Challenges of Private Higher Education in Facing Sustainable Development Goals by Implementing Sustainable Strategies - Supriyatin (International Publisher (YAPENBI), 2022)
The purpose of this study is to analyze the challenges of private tertiary institutions in Facing Sustainable Development Goals by implementing sustainable strategies. This research uses a qualitative approach with descriptive methods. The research results show that in achieving the SDGs, private tertiary institutions can carry out a typology strategy of Sustainability Report, Corporate Governance, Motivation and Incentives, Health and Safety, Human Capital Development, Ethical Behavior and Human Rights, No Conflict of Interest, No Corruption Activities and Awareness of Same , Corporate Citizen. This research is expected to be able to provide an overview of the sustainability strategies implemented by private universities in Indonesia in achieving the Sustainable Development Goals.